TOKSISITAS NANOEMULSI EKSTRAK BIJI Annona muricata DAN Leucaena leucocephala DENGAN METODE FASE INVERSI DAN HOMOGENISASI TERHADAP HAMA Spodoptera frugiperda - Ardiansyah, Sigit; Nuryanti, Ni Siluh Putu (JURNAL AGROTROPIKA, 2025)
Spodoptera frugiperda is a polyphagous insect pest that attacks corn, sorghum, soybeans, wheat, and horticultural crops. The feeding activities of S. frugiperda larvae can lead to significant economic losses for farmers. Current efforts to control S. frugiperda still rely heavily on the use of chemical insecticides. However, the excessive or inappropriate use of chemical insecticides can lead to the survival of pests that are resistant to these treatments. Bioinsecticides are considered to have lower toxicity to both living organisms and the environment, which makes them a potentially ideal option for agricultural use. This study aims to test the toxicity both individually and in combination as well as the interaction properties of a mixture of Annona muricata and Leucaena leucocephala seed extracts in various ratios as bioinsecticides against S. frugiperda in sweet corn plants. The research methods consist of rearing S. frugiperda, extraction, bioinsecticide formulation, single and mixed toxicity tests, and the interaction properties of the mixture. The results of the study showed that the method of making nanoemulsions by homogenization showed better toxicity activity compared to the method of making nanoemulsions by inversion phase. The toxicity of nanoemulsions of mixed extracts of A. muricata and L. leucocephala seeds against S. frugiperda pests at a ratio of 1:2 was more toxic than the ratios of 2:1 and 1:1. The nature of the interaction of nanoemulsions of mixed extracts of A. muricata and L. leucocephala was more dominantly antagonistic.